Caracterização hidroquímica de águas subterrâneas da Região Metropolitana do Recife-PE - Cléia Santana Chaves, Suzane (2022)
Human activities have a great influence on the quantity, as well as the quality of water available on the planet. In recent years, the demand for groundwater for various purposes has increased, making it necessary to monitor these waters, as even though they are more protected from surface pollution, the lack of control and urban expansion can result in their degradation. The present work sought to bring a study about the hydrochemical characteristics of groundwater from wells located in the Metropolitan Region of Recife, Pernambuco, according to the Piper diagram, provided by the Qualigraf program in addition to evaluating the quality of groundwater used for human consumption from wells with a grant in the period 2013-2019 database made available by the Pernambuco Agency for Water and Climate, the agency issuing grants in the state. The results indicate the classification of the waters of the analyzed wells as: 53% sodium-chlorinated, and the rest divided into: calcium-chlorinated, sodium-bicarbonate, mixed sodic, chlorinated-mixed, magnesian-chlorinated, calcium-bicarbonated, calcium- mixed, magnesian-bicarbonate, bicarbonate-mixed and mixed. Regarding the quality of water for human consumption, 87 of the 173 analyzed wells presented substances with values ​​above the permitted level in relation to the legislation, with a predominance for the parameters of total dissolved solids, nitrate, iron and chloride.